Exploring visual arts creativity through papier-mâché: artistic experiences in mask-making among elementary school students - Nur Fajrie; Hisbulloh Als Mustofa; Sulaimon Adewale (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
Visual arts education is fundamental to developing students' creativity and aesthetic awareness, yet instruction often remains confined to two-dimensional drawing and imitative tasks. This study aims to investigate the impact of papier-mâché mask-making on the artistic creativity and experiential engagement of elementary school students. Employing a mixed-methods sequential exploratory design, the research was conducted with 20 fourth-grade students at SD 3 Jepang, utilising classroom observations, interviews, and structured questionnaires to capture both the procedural and measurable aspects of artistic production. The findings reveal that students successfully navigated the stages of pre-creation, creation, and post-creation, demonstrating distinct individual expression and technical adaptation. Quantitative analysis corroborated these observations, indicating that students achieved a high level of creativity (M = 77.90) and a very high level of artistic experience (M = 81.45). The study concludes that the transformation of recyclable materials into three-dimensional forms effectively stimulates imaginative thinking and problem-solving abilities. Consequently, it is recommended that educators integrate exploratory, material-based projects into visual arts curricula to foster holistic creative development and enhance students' environmental consciousness.